Analisis Kebutuhan LKPD Berbasis Problem Based Learning tentang Materi Virus untuk Fase E SMA - Putri, Yulia Adytia; Rahmi, Yosi Laila (MASALIQ, 2023)
Quality education involves students to actively learn. It is hoped that student involvement can develop creativity that involves imagination and discovery by developing original thinking and curiosity. One of the learning media that teachers can use to support student involvement in learning is Student Worksheets (LKPD). The use of LKPD based on Problem Based Learning is expected to provide active learning conditions for students because LKPD contains a problem in everyday life that must be solved by students. The purpose of this research is to determine the level of students' needs for Problem Based Learning-based LKPD on virus material. The method used is descriptive with a qualitative and quantitative approach. The instruments used were interview sheets and questionnaires. Data collection was carried out through interviews with a biology teacher and distributing questionnaires to 60 Phase E students. The results of the research showed that there was a need to develop Problem Based Learning-based LKPD on virus material for High School Phase E as a learning medium to support the biology learning process.